Comprehensive Design of the High-Sulfur-Loading Li–S Battery Based on MXene Nanosheets - Zhang, Shouzheng; Zhong, Ning; Zhou, Xing; Zhang, Mingjie; Huang, Xiangping; Yang, Xuelin; Meng, Ruijin; Liang, Xiao (Nano-micro letters, 2020)
Highlights The intrinsic negatively charged MXene nanosheets were assembled to the positively charged Ketjen black/sulfur (KB/S) or KB to constructing the interwoven composite. The KB/S@Ti 3 C 2 T x architectures allow high sulfur loading and accommodate the corresponding volume change, while the structural integrity and the ionic and electric conducting pathways are well maintained. The KB@Ti 3 C 2 T x interlayers further retard the polysulfide that escaped from the cathode. It is only 0.28 mg cm −2 in density and 3 μm in thickness—the effect on energy density is minimal. The lithium-sulfur battery is the subject of much recent attention due to the high theoretical energy density, but practical applications are challenged by fast decay owing to polysulfide shuttle and electrode architecture degradation. A comprehensive study of the sulfur host microstructure design and the cell architecture construction based on the MXene phase (Ti 3 C 2 T x nanosheets) is performed, aiming at realize stable cycling performance of Li–S battery with high sulfur areal loading. The interwoven KB@Ti 3 C 2 T x composite formed by self-assembly of MXene and Ktejen black, not only provides superior conductivity and maintains the electrode integrality bearing the volume expansion/shrinkage when used as the sulfur host, but also functions as an interlayer on separator to further retard the polysulfide cross-diffusion that possibly escaped from the cathode. The KB@Ti 3 C 2 T x interlayer is only 0.28 mg cm −2 in areal loading and 3 μm in thickness, which accounts a little contribution to the thick sulfur electrode; thus, the impacts on the energy density is minimal. By coupling the robust KB@Ti 3 C 2 T x cathode and the effective KB@Ti 3 C 2 T x modified separator, a stable Li–S battery with high sulfur areal loading (5.6 mg cm −2 ) and high areal capacity (6.4 mAh cm −2 ) at relatively lean electrolyte is achieved.